Using opioids in general practice for chronic non‐cancer pain: an overview of current evidence. Issue 8 (2nd May 2016) - Currow, David C; Phillips, Jane; Clark, Katherine
Summary: Chronic non‐cancer pain (lasting more than 3 months) is highly prevalent in Australia (17% of males and 20% of females) and its optimal management is crucial to the health and wellbeing of the community. For 5% of the population, such pain interferes markedly with daily function. Part of the treatment for acute non‐cancer pain for many people will include opioid analgesics at least for days to weeks. However, as pain becomes chronic, evidence to support ongoing prescription of opioids is lacking. There is increasing pressure to ensure that prescribing opioid analgesics is minimised to reduce not only the risk of dependence and illicit diversion but also the potential harms associated with tolerance, side effects and complications. Frameworks for considering opioid prescribing include assessing suitability of the patient for opioids; initiating a trial of therapy; and monitoring long term use. There is limited evidence of the long term efficacy of opioids for chronic non‐cancer pain, and documented clinical consequences beyond addiction include acceleration of loss of bone mineral density, hypogonadism and an association with increased risk of acute myocardial infarction. Careful clinical selection of patients can help optimise the evidence‐based use of opioids for chronic non‐cancer pain: ► only treat pain that has been as well defined as possible when non‐opioid therapies have not been effective; ► consider referral to specialist services for assessment if doses are above 100 mg oral morphine equivalent per 24 hours or the duration of therapy is longer than 4 weeks; ► limit prescribing to only one practitioner; ► seek an agreement with the patient for the initiation and potential withdrawal of opioids if the therapeutic trial is not effective.